Economic Gap Analysis of West Kalimantan Border Region - Deffrinica Deffrinica; Maryunani Maryunani; Devanto Shasa Pratomo; Iswan Noor (JOURNAL OF MANAGEMENT, ACCOUNTING, GENERAL FINANCE AND INTERNATIONAL ECONOMIC ISSUES, 2025)
Economic inequality is a crucial issue, especially in border areas where economic development is often uneven. This study analyzes the Theil Index to measure economic disparity in border areas of West Kalimantan from 2019 to 2023. The findings reveal that Sanggau Regency consistently has the highest Theil Index, reaching 4.307 in 2021, indicating severe economic inequality. Kapuas Hulu Regency also exhibits an increasing trend, with its Theil Index reaching 2.429 in 2023, suggesting widening disparities. Meanwhile, Sambas and Bengkayang Regencies maintain relatively stable and lower indices, indicating more evenly distributed economic conditions. Singkawang City, as an economic hub, shows fluctuating inequality trends but remains among the higher indices. This research contributes a novel perspective by focusing on economic inequality in border areas, which has often been discussed at the national level rather than in localized studies. The findings highlight the unique economic challenges faced by border regions, emphasizing the need for more inclusive policies, infrastructure development, and cross-border economic optimization to ensure equitable economic growth in West Kalimantan’s border areas.